2018
DOI: 10.1021/acssuschemeng.8b00497
|View full text |Cite
|
Sign up to set email alerts
|

Green and High-Efficiency Production of Graphene by Tannic Acid-Assisted Exfoliation of Graphite in Water

Abstract: A green and high-efficiency method was developed to prepare low-cost and high-quality graphene on a large scale through direct exfoliation of graphite in aqueous media using tannic acid (TA) as the stabilizer. The influence of preparation parameters on graphene concentration (C G ) and graphite exfoliation efficiency (C G /C G,i ), including TA concentration (C TA ), initial graphite concentration (C G,i ), pH, ionic strength, sonication time, and cycles, was systematically investigated. Under the optimum cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 43 publications
4
81
0
Order By: Relevance
“…These values are appreciably greater than the theoretical thickness of monolayer graphene (0.334 nm) because of the attached SMA molecules on the surface and the folded structure of the material. Actually, similar observations are reported in other AFM studies [12,23,26]. Therefore, it could be concluded that the graphene produced by SMA-assisted microfluidization is mainly a few-layer (less than 5) structure with a lateral size of 0.5-0.9 μm, which is consistent with the TEM results.…”
Section: Characterization Of As-prepared Graphenesupporting
confidence: 91%
See 1 more Smart Citation
“…These values are appreciably greater than the theoretical thickness of monolayer graphene (0.334 nm) because of the attached SMA molecules on the surface and the folded structure of the material. Actually, similar observations are reported in other AFM studies [12,23,26]. Therefore, it could be concluded that the graphene produced by SMA-assisted microfluidization is mainly a few-layer (less than 5) structure with a lateral size of 0.5-0.9 μm, which is consistent with the TEM results.…”
Section: Characterization Of As-prepared Graphenesupporting
confidence: 91%
“…The results presented in Figure 3b demonstrate that maximum values of C G are attained at C SMA = 10 mg·mL −1 , irrespective of the number of microfluidization cycles. A higher concentration of SMA will not promote further increase in C G because of the graphene surface that becomes saturated with adsorbed SMA molecules [23].…”
Section: Optimization Of the Exfoliation Processmentioning
confidence: 99%
“…Although researchers have studied PR/graphene composites in detail, all the previous PR/graphene composites were maded of GO/rGO. Because of its structural defects, the properties of GO/rGO are far inferior to those of pristine graphene (pG) . Therefore, the performance of PR/graphene composites has much room for further improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the performance of PR/graphene composites has much room for further improvement. Even worse, as a large amount of highly corrosive acids, strong oxidizing reagents and toxic reductants are used in the preparation of GO/rGO, following a series of problems such as high explosion risk, serious environmental pollution, and complex technology, the production of GO/rGO is facing more and more severe challenges with the worldwide ever‐increasing awareness of safety, and environmental protection . On this background, methods of direct exfoliation of natural graphite for producing pG, such as liquid‐phase exfoliation method, ball‐milling method, and so forth, have developed rapidly for their advantages of simplicity, safety, environmental friendliness, and high productivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation